Physician-Assisted Suicide and Euthanasia: Contrasting the American and European Approaches - Hanson, Randall K.; Mautz, Jr., R.D.; Betts, Joseph; Ramsey, Ursula (Journal of Leadership, Accountability and Ethics, 2020)
Physician-Assisted Suicide is permitted in nine states in the United States. The American approach is closely regulated, and patients must be terminally ill with less than 6 months to live. Physicians are not directly allowed to end a patient’s life as patients are required to ingest drugs by their own action. By contrast, a number of countries in Europe allow direct physician participation in ending a person’s life. This article contrasts the American approach with the European approach.